Effect of distance of loading points on long brittle crack propagation/arrest behaviour. (1st August 2013) - Handa, T; Igi, S; Endo, S; Tsuyama, S; Shiomi, H
Abstract : The effect of the distance between loading points on a long brittle crack arrest behaviour was investigated in the ultrawide duplex ESSO tests. The effect of loading conditions was also analysed. Arrest of a long brittle crack was more facilitated in the tests with a distance between loading points of 5 m than in those with 10 m. A load drop was larger in the tests with a loading point distance of 5 m than in those with 10 m. If the specimen length is 6·8 m or more, or the distance between loading points are 10 m or more in the ultrawide duplex ESSO test, the effect of the unloading stress wave on the dynamic stress intensity factor of a crack penetrating into the test plate becomes negligible, within the range of brittle crack propagation rate between 500 and 800 m s −1 .